Analysis of the Relationship between Green Technology and Sustainable Development (United Arab Emirates as a Model): Analisis Hubungan antara Teknologi Hijau dan Pembangunan Berkelanjutan (Uni Emirat Arab sebagai Model) - Basima Nyaz Mohsin Al Mohammed (Academia Open, 2025)
General Background: Green technology has emerged as a critical driver in addressing environmental degradation, climate change, and resource depletion while supporting global sustainability goals. Specific Background: The United Arab Emirates (UAE) has positioned itself as a regional leader in adopting green technologies, investing heavily in research, development, and infrastructure across energy, education, transportation, and health sectors. Knowledge Gap: Despite global interest, limited empirical research examines how national strategies, technological indicators, and innovation outputs collectively shape the UAE’s sustainable development trajectory. Aims: This study aims to analyze the relationship between green technology and sustainable development in the UAE, focusing on its policies, applications, and challenges. Results: Findings reveal that increased R&D expenditure, growth in scientific publications, expansion of renewable energy projects, and rising patent registrations significantly contributed to advancing smart cities, energy efficiency, and environmental sustainability. Novelty: The research provides an integrated assessment of technological, economic, and institutional dimensions, offering a comprehensive view of how green technology drives sustainability in an Arab context. Implications: The study highlights the UAE’s experience as a transferable model for emerging economies, emphasizing the need for continuous investment, policy alignment, and private-sector engagement to strengthen the global transition toward sustainable development.Highlight : Green technology plays a key role in achieving sustainable development in the UAE. Smart city projects and renewable energy are main applications of green technology. Research, development, and patents strengthen innovation and sustainability. Keywords : Green Technology, Sustainable Development, Smart City, Renewable Energy, Patents